РОЗВИТОК ACARTIA CLAUSI (COPEPODA) І NOCTILUCA SCINTILLANS (DINOFLAGELLATA) В ПРИБОСФОРСЬКИХ РАЙОНАХ ЧОРНОГО І МАРМУРОВОГО МОРІВ У ПЕРІОД 2005 - 2009 РР - Губарєва, О. С.; Свєтлічний, Л. С.; Iшиннбiлiр, М. (Marine Ecological Journal, 2023)
The dynamics of Noctiluca scintillans and Acartia clausi numbers in the Bosphorus area of the Black and Marmara Seas during 2005 – 2009 has been analyzed. Positive correlations between the numbers of A. clausi and N. scintillans in the Marmara Sea near the Bosphorus and those near the Prince Islands and lack of correlation between the numbers of these species in the Marmara Sea and those in the Bosphorus area of the Black Sea indicate that A. clausi and N. scintillans form independent populations in the north-western Marmara Sea. The abundance of N. scintillans near the Bosphorus in the Marmara Sea has been 10-fold higher than that in the Black Sea. High correlation (r = 0.84) between the number of N. scintillans and that of dead A. clausi near the Bosphorus in the Marmara Sea seems to be evidence of significant role of necrozooplankton in the development of studied dinoflagellate.